(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Set expressions play a significant role in stylistics as fixed or semi-fixed combinations of words that carry specific meanings and stylistic functions. These expressions include idioms, proverbs, clichés, collocations, and phraseological units. Their use enhances the expressiveness, emotional coloring, and cultural depth of a text. In stylistics, set expressions are analyzed in terms of their semantic, structural, and functional characteristics.